Utazási szokások vizsgálata Hódmezővásárhelyen - Gál, József; Kelemen, László; Szeri, István (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Tisza Volán Zrt. made passenger counting and questionnaire poll collaborating with Szegedi Tudományegyetem, concerned with the service in order to obtain information on the travel habits of Hódmezővásárhely population related passenger from satisfaction. The result of the survey has an effect on the framing of the city's public transport. It passed since it under years actual results emerged.